Factors Influencing Teachers’ Intention to use Game-Based Learning in Secondary Mathematics - Stephen Jhon C. Arellano; Jonny B. Pornel; Raphael V. Belleza; Aileen C. Chong (Jurnal Inovasi Matematika, 2026)
Games are increasingly used to enhance mathematics instruction and improve educational quality, as research shows they can boost student motivation and learning. However, effective implementation requires teachers to have adequate knowledge and pedagogical skills in game-based learning (GBL). This survey study investigated factors influencing secondary mathematics teachers’ intentions to use GBL. The study involved 47 secondary mathematics teachers from five public high schools in Kalibo, Aklan, Philippines, and examined their intentions, motivations, deterrents, needs, and skills related to GBL. Teachers’ intentions were measured using Likert scales assessing attitudes, subjective norms, and perceived behavioral control, while proficiency was also measured through Likert scales. Motivations, deterrents, and needs were gathered using open-ended questions. Results showed a high overall intention among teachers to use GBL. Key motivations included promoting fun, active learning, resource suitability, and interactive technology. Major deterrents were time constraints, lesson suitability issues, potential distractions, and student participation challenges. Teachers demonstrated high proficiency in GBL but expressed strong needs for further training in game design, professional development, and ICT skills. They also identified the need for financial, ICT, and game design support. Overall, teachers had positive attitudes toward GBL, along with strong subjective norms and perceived behavioral control. A significant difference in attitudes toward GBL was found when teachers were grouped by age. Finally, a predictive model showed that teachers’ attitudes and perceived behavioral control significantly influenced their intention to use GBL.